Da higienização à loucura: uma perspectiva do processo higienizador “disciplinador” - Café, Laércio de Jesus (2017)
The present study analyzes the process of social hygiene, also speculates the devices of knowledge and power, especially the ones which involves the different kinds of insanity, the idea of normal, the discourse and otherness, besides considering the exclusions and "hygiene" caused by the new political/ scientific realities, as well as its repercussion in the dominating social scene of madness. Seeking, therefore, to understand who is this Other that emerges in and of the discourse of madness, we will descant several concepts with the possibility of rereading the History of madness. To do such work, this study uses as a begin the Michel Foucault's reviews, which analyses the existing arbitrary political capitalist relations of control and how it assumes the hygienist technical-scientific rationality established at the beginning of the Modern Age and currently. Considering the modern individual, his status quo in society, going through different historical times, because every episteme, at every historical time, the mad one and madness have different truths. Now, to examine these implications from an analysis of madness through the different transformations it has undergone over the centuries, infused with distorted practices of power, authority, direction, administration, correction, and which do not always refer to general wills , But rather that of its sovereigns, we follow the consequences of these processes, especially the practices and devices that made madness what we understand today, making it necessary to penetrate the core of certain theories of Michel Foucault, among other authors. And this, at the same time, reflects on the elements of the narrative of The Alienist, Machado de Assis, relating the theme between the frontier of madness and reason in the process of social hygiene, which is a widespread social concern in the nineteenth century, And are taken by scientism. Thus, when we speak of hygiene, we do not carry out a history of bodily cleansing - which registers in itself rules of cleanliness of the body parts as hygienic practices and that present rules of cleanliness in order to propagate a corporal and civic education to the dirty body And unruly amid recognized groups and often with aesthetic purpose -; Rather, our purpose is to show a history of social cleansing, a sanitization of the body in society that has allowed for effective methods of manipulation, guidance, and control that encompasses primarily the least capable. Grounded on political and scientific theories, which went from popular to scientific, being disseminated by legal apparatuses, which end up subduing a layer of the population relative to the working class. We thus show the direction of this research, bringing together the existing elements that will give us an opening to understand the hygiene of madness in society, which make up the theoretical and methodological aspects of an analysis that continues to be current.